Examining Several Factors that Influence the Quality of Regional Financial Reporting - Muabuay, Yolanda (Journal of Economics Review (JOER), 2024)
The study focuses on the factors that affect the quality of regional financial reporting in the Papua Provincial Government. It examines the impact of regional officials, the use of information technology, and regional financial supervision on the quality of financial reports. The research is motivated by the increasing importance of public accountability in Indonesian public institutions. The study finds that the quality of regional officials and information technology significantly influence the quality of regional financial reporting, while the impact of regional financial supervision is yet to be determined. The findings highlight the significance of human resources and technology in achieving high-quality financial reporting in regional governments. This research provides valuable insights for policymakers, practitioners, and stakeholders in regional financial management and accountability.